A study of skin paddle perforators of free fibula osteoseptocutaneous flap in Hospital Universiti Sains Malaysia - Omar, Farah Hany (2017)
Background : Designing a reliable skin paddle in free fibula osteoseptocutaneous flap is critical since the flap is not only recognized for its robust amount of bone, but also provide skin paddle for soft tissue cover in long bone trauma or mandibular neoplasm. Therefore, it is important to identify the perforators and the courses to ensure the skin paddle perfusion. This study was to analyse our 17 years experiences of skin paddle perforator of free fibula osteoseptocutaneous flap in Hospital Universiti Sains Malaysia. Methodology : Retrospective data collected in all patients that underwent free fibula flap in Hospital Universiti Sains Malaysia, Kelantan from 1998 to 2014. The cases with incomplete data were excluded. The skin paddle perforators of free fibula flap type and courses documented based on anatomic location and recorded into an image guided proforma. Result : There was 156 free fibula cases were done within 17 years period, but only 109 cases were included in this study. There were 305 perforators out of 109 fibula flap. Malignant cases (33.9%) was the highest indication for free fibula flap, followed by benign (27.5%), trauma (22.0%), infection (7.3%) and others (9.2%). Tibia and mandible were the highest bone to be reconstructed, which were 32.1% each. According to leg location, middle third leg has the highest number of perforator distribution (72.8%), followed by upper third of leg (18.0%) and lastly lower third of the leg (9.2%). There were 4 types of perforators that were osteoseptocutaneous, musculocutaneous, septomusculocutaneous and musculoseptocutaneous. Osteoseptocutaneous group was the highest perforator supplying the free fibula skin paddle (40%), followed by musculocutaneous(34.4%), septomusculocutaneous (15.4%) and musculoseptocutaneous (10.2%). Among the upper leg, musulocutaneous perforator group was the highest, (49%). Meanwhile, osteoseptocutaneous perforator group was the highest in both middle (42.3%) and distal (53.5%) leg. Conclusion : A reliable skin paddle would be easily raised over middle and distal zone due to the likelihood of the presence of osteoseptocutaneous perforator. Rarely, there would be anatomical variant that the skin paddle of fibula flap will be supplied by perforator from the posterior tibial artery instead of peroneal artery.